2007
DOI: 10.1258/004947507782332991
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal protozoan and helminth infections in the Municipality San Juan y Martínez, Pinar del Río, Cuba

Abstract: A cross-sectional study was carried out to determine the prevalence of intestinal parasitic infections and the intensity of soil-transmitted helminths (STHs) among children who attend the educational centres of San Juan y Martinez, Cuba. Ascaris lumbricoides, Blastocystis hominis and Giardia lamblia were the most common parasites found, with prevalence rates of 40.5%, 38.5% and 25%, respectively. In total, 91% of children harboured at least one type of intestinal parasite. The rates and intensity of intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 0 publications
0
22
1
3
Order By: Relevance
“…In Cuba, Giardia infection in children has been widely reported (Nú ñ ez et al, 1999(Nú ñ ez et al, , 2003bMendoza et al, 2001Mendoza et al, , 2003Escobedo et al, 2007) but data on the epidemiology of, and disease burden posed by, symptomatic giardiasis in paediatric patients is scarce. The aim of the present study was to identify the risk factors associated with Giardia infection in hospitalized children in the city of Havana.…”
mentioning
confidence: 99%
“…In Cuba, Giardia infection in children has been widely reported (Nú ñ ez et al, 1999(Nú ñ ez et al, , 2003bMendoza et al, 2001Mendoza et al, , 2003Escobedo et al, 2007) but data on the epidemiology of, and disease burden posed by, symptomatic giardiasis in paediatric patients is scarce. The aim of the present study was to identify the risk factors associated with Giardia infection in hospitalized children in the city of Havana.…”
mentioning
confidence: 99%
“…For instance, Cañete et al, reported a prevalence above 38% among children who were attended to in a day care center in an urban area of Matanzas city [19]. In a cross-sectional study carried out by Escobedo et al, to determine the prevalence of intestinal parasitic infections among children at educational centers in a rural area of San Juan y Martinez, Pinar del Rio province, they found the same data of prevalence of Blastocystis [20] as were found by the researchers in the Matanzas study. On the other hand, in the second national survey of intestinal parasitic infections in Cuba, in which samples of all age groups were collected, the frequency of this protozoan was 8.89% [12].…”
Section: Discussionmentioning
confidence: 85%
“…When the awareness of Giardia infection among caregivers in Havana, 33,34 its increased prevalence among children, [3][4][5][6][7][8][9] and its occurrence within the community, 2 which may also be a cause of hospitalization, 35,36 are considered, it is not surprising to find that children of mothers who knew other people with Giardia were diagnosed earlier. However, it seems that despite efforts at informing the public about intestinal parasites in Cuba, more information is necessary for addressing the giardiasis.…”
Section: Discussionmentioning
confidence: 99%
“…1 In Cuba, in the last national survey carried out in 2009, the overall prevalence of Giardia in human population was estimated to be 6.02%; 2 however, higher prevalences have been recorded among young children attending day-care centres 3,4 and primary schools, 5,6 and, according to hospital-based studies, it seems to be that clinical giardiasis is a common reason for hospitalization in paediatric hospitals. [7][8][9] As in other diseases, the diagnosis of giardiasis critically depends on the community's perception of the disease, care-seeking behaviour of individuals, socio-economic factor, and the suspicion index of the health care providers.…”
Section: Introductionmentioning
confidence: 99%